Support Services and the Division I Student-Athlete: Experiences, Needs, and Implications - Meyer, Barbara B. (My University, 1993)
This paper examined typical support service experiences of Division I football and men's basketball players. Specifically, the paper provided insight into the types ot support services generally received by Division I revenue-producing sport student-athletes, discussed perceptions of these services and the service providers, and offered opinions on how future student-athletes might be better served. The author interviewed 26 former athletes from football and men's basketbal who graduated from a particular institution about academic support, career support, support personnel, and mising links. They shared their thoughts on their advisors and tutors, location of support services, time of day to access support, whether or not study hall was effective, and other topics of interest (e.g., drug and alcohol awareness). Based on these findings, both long- and short-term recommendations for athletic personnel were proposed, including the need for more in-house career development programming for athletes.
Keywords: academic support; study hall; football; basketball